2000
DOI: 10.1309/g98j-ana9-rmnc-xlyu
|View full text |Cite
|
Sign up to set email alerts
|

Short Activated Partial Thromboplastin Times Are Related to Increased Thrombin Generation and an Increased Risk for Thromboembolism

Abstract: This prospective study was designed to investigate whether patients with short activated partial thromboplastin times (aPTTs) have increased thrombin generation and are at increased risk for thromboembolism. During a 4-month period, routine coagulation specimens were screened for the presence of a short or normal aPTT, and, accordingly, 250 specimens were collected. Prothrombin fragment F1 + 2 (F1 + 2) was measured to evaluate thrombin activation, and a second aPTT was performed with a different reagent. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 9 publications
10
57
1
Order By: Relevance
“…These results are biologically plausible because shortened APTTs have been associated with high levels of biochemical markers of thrombin generation and fibrin deposition such as prothrombin fragment 1 ϩ 2, thrombin-antithrombin complex, and D-dimer, 15,16 as well as with a poor prognosis for thrombosis and mortality in patients admitted over time to a general medical center. 17 Furthermore, the APTT is a global test responsive to the plasma levels of coagulation factors of the contact (factor XII, prekallikrein, and high-molecular-weight kininogen) intrinsic (factor XI, VIII, IX) and common (factor X, V, II and fibrinogen) pathways of blood coagulation.…”
Section: Discussionmentioning
confidence: 94%
“…These results are biologically plausible because shortened APTTs have been associated with high levels of biochemical markers of thrombin generation and fibrin deposition such as prothrombin fragment 1 ϩ 2, thrombin-antithrombin complex, and D-dimer, 15,16 as well as with a poor prognosis for thrombosis and mortality in patients admitted over time to a general medical center. 17 Furthermore, the APTT is a global test responsive to the plasma levels of coagulation factors of the contact (factor XII, prekallikrein, and high-molecular-weight kininogen) intrinsic (factor XI, VIII, IX) and common (factor X, V, II and fibrinogen) pathways of blood coagulation.…”
Section: Discussionmentioning
confidence: 94%
“…One prospective clinical study found that a short APTT is related to a 10-fold increased incidence of thromboembolic events [8]. A recent prospective study demonstrated ten Boekel/Bartels First aid 91 45 50 50 Cardiology 22 11 8 8 Intensive care unit 40 20 21 21 Neurology 8 4 2 2 Internal medicine 18 9 14 14 Oncology 2 1 0 0 Others 21 10 5 5 that patients with short APTTs are at increased risk for thromboembolism, in particular venous thrombosis (odds ratio: 5.4) [9]. Reddy et al [10] reported that approximately 25% of patients with short APTTs will develop thrombotic events within 1 year after detection, whereas in the control group the incidence was less than 3%.…”
Section: Introductionmentioning
confidence: 99%
“…10 Both dabigatran (1) and compound 2 were found to exhibit good functional activity in this coagulation assay in human plasma (2 × APTT = 0.63 and 0.23 μM, respectively). Compound 10 possessed anticlotting activity (2 × APTT = 6.9 μM) roughly 10-fold less potent than dabigatran.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 82%